Challenges to wheat disease resistance and current global strategies - Singh, Ravi P.; Hodson, David P.; Pawan Kumar Singh; Caixia Lan; Xinyao He; Lagudah, Evans S.; Juliana, Philomin; Ayliffe, Michael A.; Bhavani, Sridhar; Saunders, Diane G.O.; Huerta-Espino, Julio (Annual Reviews Inc., 2025)
Wheat yields have continued to increase globally at a steady pace over the past decade despite challenges faced by breeding programs from evolving and migrating races of rust and other wheat disease-inducing fungi. Additionally, pathogens are becoming tolerant to fungicides because of their injudicious use. We highlight the challenges in breeding and deploying resistant varieties and discuss global strategies to protect wheat from diseases. The continuous identification, utilization, and deployment of diverse resistance genes and quantitative trait loci for durable adult plant resistance, supported by precision phenotyping, marker-assisted and genomic selection, real-time pathogen diagnostics, and the rapid diffusion of resistant varieties, are helping to minimize crop losses while enhancing productivity. The potential for genetic engineering, including the introduction of resistance gene cassettes and precise genome editing of susceptibility or resistance genes, has also increased because of the recent acceptance of genetically modified wheat carrying the HB4 (R) drought tolerance gene in some countries.